The Herschel SPIRE Fourier Transform Spectrometer Spectral Feature Finder – V. Rotational measurements of NGC 891. Issue 3 (7th November 2020) - Benson, Chris S; Spencer, L D; Valtchanov, I; Scott, J; Hładczuk, N
ABSTRACT: The ESA Herschel Spectral and Photometric Imaging Receiver (SPIRE) Fourier Transform Spectrometer (FTS) Spectral Feature Finder (FF) project is an automated spectral feature fitting routine developed within the SPIRE instrument team to extract all prominent spectral features from all publicly available SPIRE FTS observations. In this work, we demonstrate the use of the FF information extracted from three observations of the edge-on spiral galaxy NGC 891 to measure the rotation of N ii and C i gas at far-infrared frequencies in complement to radio observations of the [H i ] 21-cm line and the CO(1-0) transition as well as optical measurements of H α . We find that measurements of both N ii and C i gas follow a similar velocity profile to that of H i and H α showing a correlation between neutral and ionized regions of the interstellar medium in the disc of NGC 891.